Kualitas Pelayanan Pembuatan Akta Kelahiran di Dinas Kependudukan dan Pencatatan Sipil Kota Surabaya - Putri Rahmadhani, Adibah (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
The background of this research is that one of the development steps in Indonesia is the high population level. This study aims to improve the quality of public services, especially at the Surabaya City Population and Population Registration Office for birth certificate services. The method used is the type of research used in this research is quantitative research using survey methods. Results and discussion Overall the quality of service at the Surabaya City Population and Civil Registration Office shows that the difference or gap between customer expectations and employee performance has an average total that is at the medium classification level or the quality of service at the Surabaya City Population and Civil Registration Service is quite good. This means that customer satisfaction in terms of the quality of services provided at the Department of Population and Civil Registration of the City of Surabaya is quite good.